Use of speaking strategies in Arabic by Chinese translators in communicating with Arab traders in Quangzhou and Yiwu, China - Ma, Lina (2019)
With the growth of trading in southeast China in recent years, the number of Arab tradesmen has been increased. In the result, the demand on translators to facilitate communication with Arab tradesmen has also been increased. Chinese translators face challenges when communicating with Arab tradesmen due to the structural difficulties between Arabic and Chinese languages such as the differences in grammatical rules and formulation of speech. Studies showed the possibility of overcoming these difficulties, specifically verbal difficulties that occur during speaking, by using steps or methods called speaking strategies. This research aims to investigate the use of speaking strategies in Arabic by Chinese translators with Arab tradesmen throughout a set of objectives: 1) to identify the types of speaking strategies and their use level by Chinese translators with Arab tradesmen; 2) to analyze the differences in the use of speaking strategies between male and female translators; 3) to analyze the differences between three groups of age (21-25, 26-30, 31-above) in the use of speaking strategies. A descriptive quantitative methodology is used to carry out this research. Data collection is conducted using a questionnaire. The questionnaire is modified to satisfy the objectives of this study, and two experts from a related area of this research verified this questionnaire. Sixty-eight translators from Guangzhou and Yiwu participated in this study. The data are analyzed using SPSS. The results show that all the translators have used all the speaking strategies while dealing with Arab tradesmen. Also, the results show that the strategy which required negotiating the meaning is the most frequently used. The results also showed that male translators used speaking strategies more than female translators. Finally, the translators from the youngest group of age used the strategies more than elder groups. The researcher recommends contacting more research in different fields to develop the ability to speak and communicate using optimal speaking strategies. The study can also be expanded by increasing adding other data collection tools. This helps to enhance language learning and expand speaking strategies to be a secondary sub-field of language acquisition and a solution for linguistics issues.